2022
DOI: 10.3389/fpls.2022.842317
|View full text |Cite
|
Sign up to set email alerts
|

High CO2 Reduces Spoilage Caused by Botrytis cinerea in Strawberry Without Impairing Fruit Quality

Abstract: High CO2 (> 20 kPa) conditions are beneficial for suppressing spoilage caused by Botrytis cinerea in strawberry fruit; however, these conditions are often accompanied by discoloration, off-flavors, and faster softening. Stepwise increments of CO2 concentrations have been proposed to alleviate injuries in fruits caused by high CO2. In this study, we investigated whether stepwise increments of CO2, up to 30 kPa and under a reduced O2 concentration, are beneficial for reducing fungal spoilage without induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…Among these, avoiding condensation inside packages is crucial, because it has been extensively demonstrated that this phenomenon plays a key role in mould growth and decay [55]. In addition, acting on internal gaseous atmospheric composition has been reported to be a successful strategy, where reductions of O 2 concentration to 10% and increased CO 2 concentration (15%-20%) can help limit Botrytis growth [56]. This can be explained by a reduced strawberry metabolic rate due to reduced O 2 concentrations, thus delaying senescence, whereas high CO 2 concentrations exhibit bacteriostatic and fungistatic effects.…”
Section: Microbiological Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, avoiding condensation inside packages is crucial, because it has been extensively demonstrated that this phenomenon plays a key role in mould growth and decay [55]. In addition, acting on internal gaseous atmospheric composition has been reported to be a successful strategy, where reductions of O 2 concentration to 10% and increased CO 2 concentration (15%-20%) can help limit Botrytis growth [56]. This can be explained by a reduced strawberry metabolic rate due to reduced O 2 concentrations, thus delaying senescence, whereas high CO 2 concentrations exhibit bacteriostatic and fungistatic effects.…”
Section: Microbiological Qualitymentioning
confidence: 99%
“…In packaging experiments, Botrytis or other pathogens, if present, are usually quantified by visual inspection, determining ‘fungal decay’ or ‘decay incidence’ as the number of decayed fruits over the total number of fruits in a package (%) [47, 56]. Strawberry microbiological quality can also be characterized in terms of total aerobic mesophilic counts, yeast and mould counts and coliforms [57, 58].…”
Section: Main Factors Limiting Fresh Strawberry Shelf Lifementioning
confidence: 99%
“…Soil sterilization at 55°C for 15 min proved lethal to Botrytis spp. It is clear that greenhouse conditions are easier to handle with field-grown strawberries, however some other techniques can be applied to both field and greenhouse crops; good soil drainage, putting straw mulches or polythene cover to reduce the plant and soil-surface contact (Legard et al, 2000 andFedele et al, 2020), choosing the correct time and rate of fertilizer applications, weeds management (weeds increase the infection of Botrytis spp., impede air circulation, and can be a source of inoculum), eliminating of rotten strawberries frequently and remove them away (Legard et al, 2000 andWilliamson et al, 2007), planting in raised beds and effective pruning (Legard et al, 2000;Li et al, 2022 andXiao et al, 2022).…”
Section: Disease Managementmentioning
confidence: 99%
“…A delay of one hour highlighted the amplification of post-harvest losses due to grey mould. Storage at these low temperatures is essential to retard grey mould and slow fruit respiration (Droby et al, 2009;Feliziani andRomanazzi, 2016 andLi et al, 2022).…”
Section: Disease Managementmentioning
confidence: 99%
See 1 more Smart Citation